Evaluation of the use of CGRP monoclonal antibodies (mAbs) in migraine prophylaxis in a private clinic - Farenzena, Natalia; Fröhlich, Alan Christmann (Headache Medicine, 2023)
Introduction Migraine is considered the second most prevalent neurological disorder in the population and highly disabling. Objective The aim of this study is to evaluate the use of calcitonin gene-related peptide (CGRP) monoclonal antibodies in migraine prophylaxis, with emphasis on therapeutic response, adverse effects, and impacts on quality of life. Method A quantitative, retrospective, and descriptive study was carried out, through the analysis of medical records and telephone interviews with patients seen at the Serviço de Neurologia e Neurocirurgia, in the city of Passo Fundo, RGS, Brazil, currently or previously having used at least one dose of the medication. Conclusion Thus, it is understood that CGRP monoclonal antibodies are able to reduce monthly headache days, reduce pain intensity and promote improvement in work capacity. Therefore, they can be considered effective, safe and well-adhered medications for migraine prophylaxis.